Estudio de factibilidad para la creación de una agencia de viajes en la ciudad de Chaguarpamba, cantón Chaguarpamba, provincia de Loja. - Bustos Carrión, Andrés Marcelo (2018)
The title of this research work is: "STUDY OF FEASIBILITY FOR THE CREATION OF A TRAVEL AGENCY IN THE CITY OF CHAGUARPAMBA, CANTON CHAGUARPAMBA, PROVINCE OF LOJA", aims to conduct a feasibility study for the creation of a travel agency in the city of Chaguarpamba, Canton Chaguarpamba, province of Loja, in view of the fact that in this city and province there is a high percentage of national and foreign tourists who come to the province of Loja. The methodology used for this thesis project was: The analytical, descriptive, inductive, deductive, statistical method and the techniques used were the survey of a sample of 388 domestic and foreign tourists who come to the province of Loja and an interview with the representative of a travel agency of Chaguarpamba. Among the main results we have a potential demand of 12665.82; actual demand of 7907.58; effective demand 2646.67, an offer of 1066.58 services and an unsatisfied demand of 1580.09. With regard to the marketing plan, it has been established that the company's commercial channel to the client or user, without using any intermediary. In the technical study, there is an installed capacity of 1300 and a used capacity of 75% or 975. In the administrative-legal study, the organizational structure of this agency is considered as structural, functional and positional, and the manual of functions for each of the required positions has been described. The total investment required for the start-up of this agency is $ 24132.08, whose financing will be 62.16% with a 5-year BanEcuador loan; the expected income will be for the first year of $ 112625.00 Regarding the Financial Evaluation, a NPV of $ 53577.28 was obtained, a TIR of 30.90%, the Benefit / Cost Ratio is of $ 1.24, the PRC will be of 3 years, 8 months and 27 days, the Sensitivity analysis with an increase of 10.85% in costs, the Sensitivity Analysis with a 9.00% decrease in income, which indicates that the project is feasible. The results obtained showed us that there is an unmet demand from a Travel Agency in Chaguarpamba; and finally conclusions and recommendations were determined.